Index — volume 24 — 1969 (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le discours de Paul VI à l’O.I.T. (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les relations du travail au Canada (Rapport Woods) (Relations industrielles / Industrial Relations, 1969)
Le 21 mars 1969, l'Équipe spécialisée en relations du travail, Ottawa, déposait son rapport au bureau du Conseil privé. Rappelons que la direction de cette Commission avait été confiée à H.D. Woods et que les membres étaient Gérard Dion, John H.G. Crispo et A.W.R. Carrothers (1). (1) Pour une présentation plus complète de la Commission et de son mandat, voirRelations industrielles, vol. 22, no 1, 1967, pp. 130-136.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Loi des relations du travail dans l’industrie de la construction (bill 290) (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Reform of British Industrial Relations : The Donovan Report and the Labour Government’s Policy Proposals - Banks, Robert F. (Relations industrielles / Industrial Relations, 1969)
Against a background of recurrent economic crisis in the 1960s pressures have developed to reform Britain's traditional industrial relations system. During the last two years the report of The Royal Commission on Trade Unions and Employers' Associations and a subsequent Labour Government White Paper included significant recommandations which are likely to change the character of the traditional system. Nevertheless both documents support an essentially voluntary approach to the reform of collective bargaining and reject the transformation of collective agreements into legally binding contracts. However, as a result both of growing public support for additional reforms and the improvement in the Conservative Opposition's political fortunes, plus doubts about the capacity of British unions and management to improve collective bargaining procedures voluntarily, the author suggests that further Government intervention in industrial relations is a strong possibility in the next few years.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Wage Comparisons and Productivity - Beach, E. F. (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Fringe Benefits : Wage or Social Obligation - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "Fringe Benefits : Wage or Social Obligation" by Donna Allen.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Lexique de l’information - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "Lexique de l’information" by J. Guilhaumou.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Japan’s Managerial System : Tradition and Innovation - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1969)
This article reviews "Japan’s Managerial System : Tradition and Innovation" by M.Y. Yoshino.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Manpower Planning for High Talent Personnel - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1969)
This article reviews "Manpower Planning for High Talent Personnel" by Eric W. Vetter.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Organizational Behavior - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1969)
This article reviews "Organizational Behavior" by Joe Kelly.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Readings in Organizational Behavior and Human Performances - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1969)
This article reviews "Readings in Organizational Behavior and Human Performances" by L.L. Cummings and W.E. Scott.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Mobile Manager : A Study of the New Generation of Top Executives - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1969)
This article reviews "The Mobile Manager : A Study of the New Generation of Top Executives" by E.E. Jennings.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

White and Blue-Collars in a Mill Shutdown - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1969)
This article reviews "White and Blue-Collars in a Mill Shutdown" by Felician F. Foltman.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le service d’entretien, méthodes actuelles de gestion - Bernard, Michel (Relations industrielles / Industrial Relations, 1969)
This article reviews "Le service d’entretien, méthodes actuelles de gestion" from the Entreprise Moderne d’Édition (Paris).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Mission of Manpower Policy - Bernard, Michel (Relations industrielles / Industrial Relations, 1969)
This article reviews "The Mission of Manpower Policy" by E. Wight Bakke.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Collective Bargaining Clauses, Guideline Forms for Use in Labor Negotiations - Bernier, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "Collective Bargaining Clauses, Guideline Forms for Use in Labor Negotiations" by Robert C. Knee and Robert C. Knee Jr.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Essays in Labour History - Bernier, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "Essays in Labour History" by Asa Briggs and John Saville.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Histoire et politique du droit du travail - Bernier, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "Histoire et politique du droit du travail" by P. Virton.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’extension des conventions collectives dans le droit du travail : France, Grande-Bretagne et Canada - Bernier, Jean (Relations industrielles / Industrial Relations, 1969)
Après avoir fait un rappel historique des circonstances qui ont entouré l'instauration des régimes de conventions collectives étendues dans les trois pays considérés, l'auteur procède à une étude comparative des législations en ce domaine. Il considère les dispositions relatives aux conventions susceptibles d'extension, à la procédure d'extension, aux effets de l'extension et à l'application des conventions étendues. Il accorde une attention particulière à certains aspects de la législation québécoise en cette matière.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor Law - Bernier, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "Labor Law, vol. I" by Joseph Alton Jenkins.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Un service d’information sur les conventions collectives de travail - Bernier, Jean (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Guaranteed Income for the Unemployed, The Story of SUB - Boivin, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "Guaranteed Income for the Unemployed, The Story of SUB" by Joseph M. Becker.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La sécurité des revenus face aux changements de structure - Boivin, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "La sécurité des revenus face aux changements de structure" from the Bureau international du travail (Genève).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Canadian Labour Market - Boivin, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "The Canadian Labour Market" edited by Arthur Kruger and Noah M. Meltz.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Immigrants in Industry - Brien, Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "Immigrants in Industry" by Sheila Paterson.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’homme en situation industrielle - Brien, Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "L’homme en situation industrielle" by Philippe Muller and Paul Silberer.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La C.G.T. - Brien, Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "La C.G.T." by A. Barjonet.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La France et le management - Brien, Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "La France et le management" by Roger Priouret.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Pour une doctrine de l’entreprise - Brien, Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "Pour une doctrine de l’entreprise" by Philippe de Woot.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Impact of Computers on Management - Brien, Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "The Impact of Computers on Management" edited by Charles A. Myers.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La négociation collective par secteurs et le droit québécois du travail - Cardin, Jean-Réal (Relations industrielles / Industrial Relations, 1969)
L'auteur explore l'idée de la négociation par secteurs, en discute les avantages et les inconvénients en regard des exigences de l'économie québécoise et suggère enfin certaines avenues d'évolution selon lesquelles notre droit de la négociation collective ainsi que ses mécanismes d'application pourraient être appelés à évoluer.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Trade Union Movement of Canada 1827-1959 - Cardin, Jean-Réal (Relations industrielles / Industrial Relations, 1969)
This article reviews "The Trade Union Movement of Canada 1827-1959" by Charles Lipton.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Cheminement des carrières de direction dans la fonction publique au Canada - Chartrand, Philippe J.; Pond, Kenneth L. (Relations industrielles / Industrial Relations, 1969)
Cet article présente un résumé d'une étude entreprise auprès des hauts fonctionnaires dans la fonction publique du Canada. Elle porte sur le cheminement des carrières et touche aussi à la mobilité, à l'occupation et aux sources de recrutement.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Dictionnaire de l’économie contemporaine - Dion, Gérard (Relations industrielles / Industrial Relations, 1969)
This article reviews "Dictionnaire de l’économie contemporaine" by Fernand Baudhuin.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Hommage à David A. Morse, directeur général du Bureau International du travail - Dion, Gérard (Relations industrielles / Industrial Relations, 1969)
À l'occasion du cinquantenaire de l'Organisation internationale du travail, l'université Laval, lors de la collation des diplômes le 18 octobre 1969, a tenu à marquer cet anniversaire — qui coïncidait avec le vingt-cinquième de la fondation de son département de relations industrielles — en décernant un doctorat d'honneur en sciences sociales {mention relations industrielles) à M. David A. Morse, directeur général du Bureau international du travail. Voici la citation telle que présentée par le professeur Gérard DION.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La grève-sans-arrêt-du-travail - Dion, Gérard (Relations industrielles / Industrial Relations, 1969)
Depuis longtemps on est à la recherche d'un substitut à la grève traditionnelle qui sauvegarderait le recours à l'utilisation de pressions économiques dans les négociations collectives et en même temps éviterait les inconvénients dont souffrent les consommateurs. Cette étude a pour but d'étudier l'origine, la nature, les avantages et les inconvénients d'une formule qui a été préconisée : la grève-sans-arrêt-de-travail (statutory strike).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Lexique de la psychologie, and Lexique des sciences sociales - Dion, Gérard (Relations industrielles / Industrial Relations, 1969)
This article reviews "Lexique de la psychologie" and "Lexique des sciences sociales" both by Arlette and Roger Mucchielli.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Options humanistes - Dion, Gérard (Relations industrielles / Industrial Relations, 1969)
This article reviews "Options humanistes" from the Éditions Économie et Humanisme.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Origin and Evolution of the I.L.O. and Its Role in the World Community - Dion, Gérard (Relations industrielles / Industrial Relations, 1969)
This article reviews "The Origin and Evolution of the I.L.O. and Its Role in the World Community" by David A. Morse.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Comment sont organisée les entreprises américaines - Dionne, Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "Comment sont organisée les entreprises américaines" by Ernest Dale and the American Management Association.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Formation professionnelle : plus qu’une préoccupation, une nécessité - Dionne, Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "Formation professionnelle : plus qu’une préoccupation, une nécessité" from the Conférence syndicale mondiale sur la formation professionnelle.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La mobilité des travailleurs urbains - Dionne, Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "La mobilité des travailleurs urbains" by L. Hunter and G. Reid.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La valeur ajoutée économique, - méthode pratique pour obtenir, au jour le jour, les résultats d’exploitation - Dionne, Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "La valeur ajoutée économique - méthode pratique pour obtenir, au jour le jour, les résultats d’exploitation" by Gérard Brown.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le travail intérimaire en Belgique et dans les pays du marché commun - Dionne, Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "Le travail intérimaire en Belgique et dans les pays du marché commun" par L.E. Troclet et E. Vogel-Polsky.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Mediator : Background, Self-image and Attitudes - Dionne, Pierre (Relations industrielles / Industrial Relations, 1969)
This article reviews "The Mediator : Background, Self-image and Attitudes" by Bernard P. Indik.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La politique salariale et le cycle économique - Dubé, Yves (Relations industrielles / Industrial Relations, 1969)
Dans cet exposé, l'auteur explique comment il ne croit pas plus à la politique salariale qu'il peut croire à l'inévitabilité du cycle économique. Il croit encore moins à la possibilité d'influencer le cycle économique par une quelconque politique salariale.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le choix de la sanction disciplinaire : discrétion de l’employeur ou de l’arbitre? - Dussault, René; Verge, Pierre (Relations industrielles / Industrial Relations, 1969)
Un arbitre constate que l'employeur était justifié d'imposer une sanction disciplinaire. Peut-il alors, en l'absence d'un texte exprès dans la convention collective, substituer son jugement à celui de l'employeur quant au choix de la sanction ? Un arrêt récent de la Cour suprême du Canada (1) vient de lui nier ce pouvoir. L'arbitre des griefs pourra-t-il désormais jouer pleinement son rôle ? (1) Regina v. Arthurs ex parte Port Arthur Shipbuilding Co., arrêt unanime du 1er octobre 1968, rapporté à 68 CLLC, parag. 14, 136, p. 11, 686. L'on infirme un arrêt majoritaire de la Cour d'appel d'Ontario (1967) 2 O.R. 49, qui lui-même renversait le jugement de première instance (1967) 1 O.R. 272. La décision du tribunal d'arbitrage se trouve rapportée à (1966) 17 Lab. Arb. Cas. 109 (Re.United Steelworkers and Port Arthur Shipbuilding Co.)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Essays in Money and Banking (in honour of R.S. Sayers) - Gauthier, Hervé (Relations industrielles / Industrial Relations, 1969)
This article reviews "Essays in Money and Banking (in honour of R.S. Sayers)" by C.R. Whittlesey and S.G. Wilson.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Expectations, Investment and Income - Gauthier, Hervé (Relations industrielles / Industrial Relations, 1969)
This article reviews "Expectations, Investment and Income" by G.L.S. Shackle.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Management and the Behavioral Sciences - Gauthier, Hervé (Relations industrielles / Industrial Relations, 1969)
This article reviews "Management and the Behavioral Sciences" by Maneck S. Wadia.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Organizational Psychology - Gauthier, Hervé (Relations industrielles / Industrial Relations, 1969)
This article reviews "Organizational Psychology" by Bernard M. Bass.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Law and Labour Relations : A Reaction to the Rand Report - Goldenberg, H. Carl (Relations industrielles / Industrial Relations, 1969)
After having recalled some basic principles in the field of labour relations, the author, a practician with more than thirty years of experience, deals with subjects such as the right to strike, the need for law and industrial unrest in Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Education, Employment and Utilization Patterns of French-Canadian and English-Canadian Engineering Graduates - Gross, Andrew C. (Relations industrielles / Industrial Relations, 1969)
In this article, the author compares the experience of French-speaking and English-speaking engineering graduates in Canada, focusing on similarities and differences in their education, employment and utilization patterns. This essay is based on a larger study which has dealt with engineering manpower in Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Contemporary Public Policy Issues in Industrial Relations - Hall, Noël A. (Relations industrielles / Industrial Relations, 1969)
The present system of collective bargaining is more an exercise in the use of coercive economic and political power by labour and management than a process of rational, logical argument and existing conciliation procedures have proven inadequate in reflecting the public interest in dispute settlement. What then is the impact of B.C. Bill 33 ?
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Human Resources in Canada : Changing Attitudes and Roles - Haythorne, George V. (Relations industrielles / Industrial Relations, 1969)
The author observes how Canadians have influenced and have been influenced by their environment and thus tries to understand more fully how, through individual and collective action, their participation, development and enjoyment in today's world may be more fully achieved.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Nova Scotia Labour-Management Agreements - Henson, Guy (Relations industrielles / Industrial Relations, 1969)
The Nova Scotia Joint Labour-Management Study Committee was established in May 1962. The present paper will attempt to give an account of the Committee's origins, accomplishments to date, and present activities and objectives ; methods or processes of work and some assessment of its significance.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Manpower Projections : Atlantic Canada, Some Policy Considerations - Jain, Harish C. (Relations industrielles / Industrial Relations, 1969)
This article attempts to describe, briefly, the present manpower situation in the Atlantic Region of Canada vis-a-vis the policies pursued by the federal and provincial government agencies in connection with the manpower problems of the region. Our purpose is twofold: First, to state reasons for the necessity of forecasting manpower requirements at the regional level and the relevance of manpower projections to the problems of manpower utilization. Second, to describe the methodology of forecasting manpower requirements and training needs for the Nova Scotia Department of Labour to illustrate what can and needs to be done at the regional level. Research and data gaps in the forecasting of manpower requirements and supply along with some concluding remarks form the evaluative part of this article.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Impact of Ethnic differences in the work force in Industrial Relations : A case study - Jain, Hem C. (Relations industrielles / Industrial Relations, 1969)
In light of the New Brunswick International Paper Company's experience, the author explores the effect of local conditions and of external economic and organizational factors on the process of accomodation. He also examines the degree to which all the parties involved are willing to reach accommodation in handling ethnic tension at plant level in this mill. An attempt is finally made to indicate the extent to which the finding of this case study might be applicable to other mills.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Canadian Economic System - Jean Sexton (Relations industrielles / Industrial Relations, 1969)
This article reviews "The Canadian Economic System" by André Raynauld.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Social Objectives of Economic Development - Kaplansky, Kalmen (Relations industrielles / Industrial Relations, 1969)
The author summarizes the l.L.O.'s technical co-operation activities and their evolution from the early 1930's until the present time by highlighting some of the main topics and making a few supplementary observations.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Emerging Concepts in Management - Ladouceur, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "Emerging Concepts in Management" by Max Wortman and Fred Luthans.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Managerial Process and Organizational Behavior - Ladouceur, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "Managerial Process and Organizational Behavior" by Alan C. Filley and Robert J. House-Scott.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Personnel and Industrial Relations : A Managerial Approach - Ladouceur, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "Personnel and Industrial Relations : A Managerial Approach" by John B. Miner.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Protection effective dans l’économie canadienne - Larose, Guy (Relations industrielles / Industrial Relations, 1969)
This article reviews the study "Protection effective dans l’économie canadienne" by James R. Melvin and Bruce W. Wilkinson.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Problème social et naissance du syndicalisme catholique - Maheu, Louis (Sociologie et sociétés, 1969)
Entre 1896 et 1915, au moment où le Québec connaissait un développement économique majeur, un important problème social prenait forme: l'arrivée massive des ouvriers canadiens-français sur la scène sociale et nationale. Cette situation sociale allait provoquer simultanément chez divers groupes d'acteurs - les promoteurs du syndicalisme catholique et ceux du syndicalisme international - des actions de contestation et de reconstitution des formes de la vie sociale. Le sens des attitudes et idéologies collectives de ces deux groupes d'acteurs sera dégagé des orientations normatives de leur motivation, c'est-à-dire, de ce qui les motivait à l'engagement social et qui allait être à l'origine de certaines valeurs sociales. Ces orientations, qui donnent forme et existence à leurs projets collectifs de participation à l'organisation sociale, s'avéreront non seulement contradictoires mais encore opposées.

Le Canada en tant que membre de l’O.I.T. : réalisations et possibilités - Mainwaring, John (Relations industrielles / Industrial Relations, 1969)
Après une brève présentation de l'O.I.T., l'auteur fait un inventaire de la participation canadienne à cette organisation internationale pour ensuite aboutir aux perspectives d'avenir.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

De la « politique des revenus » à une politique de répartition - Marion, Gérald (Relations industrielles / Industrial Relations, 1969)
This article reviews "De la « politique des revenus » à une politique de répartition" by J.C. Koeune, J.L. Kruseman and P. Mandy.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Unemployment, Money Wage Rates, and Inflation - Marion, Gérald (Relations industrielles / Industrial Relations, 1969)
This article reviews "Unemployment, Money Wage Rates, and Inflation" by Georges L. Perry.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Manpower Policy : Nature, Objectives, Perspectives - Meltz, Noah M. (Relations industrielles / Industrial Relations, 1969)
This article is intended to provide an overall view of the manpower field. A conceptual framework is developed for examining the various strands of the manpower field and the major government manpower programs are fitted into this framework. Suggestions for future manpower policies are also related to this framework.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Aperçu général et critique de la loi modifiant le Code du travail – 13 juin 1969 - Morin, Fernand (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’effet du vote au scrutin secret (art. 25 C.T.) préalable à l’accréditation - Morin, Fernand (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La légalité des clauses de sécurité syndicale doit-elle être encore remise en cause? - Morin, Fernand (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le pouvoir de sanction de l’arbitre de grief et le contrôle judiciaire - Morin, Fernand (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les arbitres nommés par les parties sont-ils liés par les délais de procédure établis à la convention collective? - Morin, Fernand (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Loi des relations du travail dans l’industrie de la construction - Morin, Fernand (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Employment & Economic Growth : An International Perspective - Morse, David A. (Relations industrielles / Industrial Relations, 1969)
In its anniversary year, the I.L.O. has launched a World Employment Programme. The author will examine the circumstances in which this Programme has been launched and what it must accomplish. After a brief discussion of the nature and extent of unemployment and underemployment in developing countries, the author will make some remarks on the kind of approach that these countries themselves may have to adopt in grappling with these problems. He will then present the relationship between employment and growth. Finally he will make some comments on the kind of international perspective and international programme that are needed. This papers was presented by the author at Columbia University, as part of the Gabriel Silver Memorial Lecture.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Democracy as a Goal of Union Organization : An Interpretation of the United States Experience - Muthuchidambaram, S. (Relations industrielles / Industrial Relations, 1969)
This paper presents a overall review and an interpretation of the vast existing literature on union democracy in the United States.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Teachers’ Militancy and the Changing Teacher-School Management Relationships - Nault, Aimé (Relations industrielles / Industrial Relations, 1969)
The author discusses why, and why now, teachers are becoming more militant and to what extend and how should teachers participate in policy and decision making. The present article is only part of a study made by the author.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Retraining the Unemployed - Parenteau, L.-René (Relations industrielles / Industrial Relations, 1969)
This article reviews "Retraining the Unemployed" edited by Gerald G. Somers.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Traditionnal Trade of Asia - Parenteau, L.-René (Relations industrielles / Industrial Relations, 1969)
This article reviews "The Traditionnal Trade of Asia" by G.-G.F. Simkin.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Transition from School to Work - Parenteau, L.-René (Relations industrielles / Industrial Relations, 1969)
This article reviews "The Transition from School to Work" from The Princeton Manpower Symposium.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Unemployment Insurance, the American Experience (1915-1935) - Parenteau, L.-René (Relations industrielles / Industrial Relations, 1969)
This article reviews "Unemployment Insurance, the American Experience (1915-1935)" by Daniel Nelson.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Wages in Practice and Theory - Parenteau, L.-René (Relations industrielles / Industrial Relations, 1969)
This article reviews "Wages in Practice and Theory" by Robert Ozanne.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

West Indian Migration to Britain - Parenteau, L.-René (Relations industrielles / Industrial Relations, 1969)
This article reviews "West Indian Migration to Britain" by Peach Ceri.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les cadres et la révolution informatique, l’adaptation nécessaire - Petit, André (Relations industrielles / Industrial Relations, 1969)
This article reviews "Les cadres et la révolution informatique, l’adaptation nécessaire" by Arnold Kaufmann.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Inflation, Wage Behaviour and Labor Mobility - Porter, Allan A. (Relations industrielles / Industrial Relations, 1969)
The author considers briefly the cost-push doctrine and why, if one accepts it, guidelines appear to be the logical remedy for inflation. This analysis is followed by an examination of Canadian wage behaviour, ending with particular attention to the effectiveness of the Canadian wage system in allocating manpower throughout the economy.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les conflits intersyndicaux au Québec (1957-1967) - Roberge, Pierre (Relations industrielles / Industrial Relations, 1969)
Dans cette étude, on trouve une analyse des conflits intersyndicaux survenus au Québec durant la période du 1er avril 1957 au 31 mars 1967. Deux formes de la rivalité syndicale sont distinguées : le recrutement simultané et le maraudage. L'auteur précise l'évolution de l'une et de l'au-au au cours de la dernière décennie, identifie les principaux modèles d'agression et examine le comportement des diverses organisations syndicales. Il tente en outre une comparaison entre la situation américaine en 1951-1952 et la période de pointe de la rivalité intersyndicale au Québec, 1964-1967. Il conclue en revoyant brièvement certaines caractéristiques des deux principales organisations syndicales.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Facteurs d’ambiance, rendement et humanisation du travail - Sartin, Pierrette (Relations industrielles / Industrial Relations, 1969)
Malgré la mécanisation et la modernisation des moyens de production, il reste encore beaucoup à faire pour humaniser le travail.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Growth of White-Collar Unionism and Public Policy in Canada - Sayers Bain, Georges (Relations industrielles / Industrial Relations, 1969)
The number of white-collar workers is rapidly increasing. If the trade union movement is to continue to play an effective role in the industrial relations system, it must recruit these workers. But so far, outside of the public sector of the economy, there is relatively little white-collar unionism in Canada. The major reason for this is that Canadian public policy on industrial relations is not very effective in curbing management opposition to white-collar unionism. The paper suggests several ways in which public policy might be made not only more effective in this regard but also deals with the problems arising from the growth of white-collar unionism.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor Relations in the Netherlands - Sexton, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "Labor Relations in the Netherlands" by John P. Windmuller.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les relations de travail dans l’industrie de la construction - Sexton, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "Les relations de travail dans l’industrie de la construction" under the direction of H. Carl Goldenberg and John H.G. Crispo.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Évolution économique et salut de l’homme - Solasse, Bernard (Relations industrielles / Industrial Relations, 1969)
This article reviews "Évolution économique et salut de l’homme" by M. Parodi, A. Bonety, A. Souques, G. Couvreur et P. de Surgy.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Organisation du travail dans l’entreprise - Solasse, Bernard (Relations industrielles / Industrial Relations, 1969)
This article reviews "Organisation du travail dans l’entreprise" by Neeby D. Gardener, translated and taken on by Michel de Tihef.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Ressources humaines pour le développement industriel - Solasse, Bernard (Relations industrielles / Industrial Relations, 1969)
This article reviews "Ressources humaines pour le développement industriel" from the Bureau international du travail (Genève).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Notion, objectifs, possibilités - St-Laurent, Jacques (Relations industrielles / Industrial Relations, 1969)
Après avoir défini la notion de politique de salaires, l'auteur tente d'en expliquer les objectifs et d'identifier les moyens à employer pour la rendre efficace. Mais, en fait, on parle beaucoup de politique de salaires mais que fait-on concrètement à ce sujet ?
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Nature of Price Theory - St-Laurent, Jacques (Relations industrielles / Industrial Relations, 1969)
This article reviews "The Nature of Price Theory" by H.H. Liebhapsky.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Wage Policy - St-Laurent, Jacques; Tremblay, Marc-Adélard; Dubé, Yves (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Canadian Industrial Relations – The Task Force Report - Sturmthal, Adolf (Relations industrielles / Industrial Relations, 1969)
After an overall judgment of the Report, the author examines problems such as the emergency strike, the alienation of the worker, the long-term full employment, inflation, industrial democracy, union certification, union security and wage parity.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les implications salariales des comportements de consommation - Tremblay, Marc-Adélard (Relations industrielles / Industrial Relations, 1969)
L'auteur tente ici de traduire la manière dont le consommateur se conçoit lui-même, essaie de faire ressortir les pressions qui s'exercent sur ce dernier et définit les ressources dont il devrait disposer pour se procurer les biens et services qu'il juge nécessaires.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Admissibilité du recours civil de l’ex-salarié, fondé sur la convention collective - Verge, Pierre (Relations industrielles / Industrial Relations, 1969)
Un salarié quitte son emploi et prétend que l'employeur n'a pas observé la convention collective à son endroit. En l'occurence, il s'agit de la liquidation des congés-maladie accumulés. En est-il réduit à tenter d'amener un arbitre à trancher la difficulté ? A-t-il, au contraire, accès au tribunal civil ? La Cour d'appel vient de lui reconnaître cette dernière avenue (1) L'intégrité de la compétence de l'arbitre des griefs serait-elle à nouveau atteinte ?
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Amendements au Code du travail du Québec (Bill 50) - Verge, Pierre (Relations industrielles / Industrial Relations, 1969)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’entre-temps des conventions collectives - Verge, Pierre (Relations industrielles / Industrial Relations, 1969)
La succession des conventions collectives est loin de se faire toujours de façon ininterrompue. L'absence d'un régime transitoire, selon le Code du travail, peut laisser place souvent à un « vide juridique », à l'expiration d'une convention collective. Nous examinons dans cette perspective la limitation de la durée de la convention collective et les conséquences qu'elle entraîne.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le rattachement de l’accréditation et de la convention collective à l’entreprise - Verge, Pierre (Relations industrielles / Industrial Relations, 1969)
Le rattachement de l'accréditation et de la convention collective à l'entreprise préserve assez efficacement le pouvoir de représentation de l'association de salariés et, le cas échéant, le régime collectif de travail établi avec le concours de cette dernière.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les aspects constitutionnels de la ratification des conventions de l’O.I.T. - Wanczycki, Jan K. (Relations industrielles / Industrial Relations, 1969)
Le problème de la ratification des conventions de l'O.I.T. par les états fédératifs s'est toujours posé. Après une brève présentation de l'Acte de l'Amérique du Nord britannique, l'auteur examine plus particulièrement le cas du Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z